2021
DOI: 10.3389/fvets.2021.628241
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Global DNA Methylation in Canine Mammary Gland Tumors via Immunostaining of 5-Methylcytosine: Histopathological and Clinical Correlations

Abstract: Mammary tumors are the most prevalent neoplasms in non-neutered female dogs, with genetic and epigenetic alterations contributing to canine mammary carcinogenesis. This study quantified global DNA methylation in 5-methylcytosine (5mC)-immunostained canine mammary tumor samples and established histopathological and clinical correlations. A total of 91 formalin-fixed paraffin-embedded mammary tumor samples from female dogs were retrospectively selected and subjected to immunohistochemistry using an anti-5mC mous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…In contrast (18,19,30), demonstrated that the most aggressive tumor subtypes have shown predominant weakly stained nuclei that presumably revealed global DNA hypomethylation. Unfortunately, in this study, we could not evaluate the normal methylation pattern of canine mucosal melanocytes, since these cells are roughly seen in histological sections of oral mucosa in clinically healthy dogs.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In contrast (18,19,30), demonstrated that the most aggressive tumor subtypes have shown predominant weakly stained nuclei that presumably revealed global DNA hypomethylation. Unfortunately, in this study, we could not evaluate the normal methylation pattern of canine mucosal melanocytes, since these cells are roughly seen in histological sections of oral mucosa in clinically healthy dogs.…”
Section: Discussionmentioning
confidence: 91%
“…The OMM slides were analyzed in an image analysis system to quantify strong, weak, or negative nuclei (at least 500 per case). The same quantification approach was used in other studies ( 18 , 19 , 30 ). The results of these quantifications showed that both melanotic and amelanotic OMMs presented higher percentages of weakly stained and negative 5mC nuclei.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a broader analysis, Biondi et al (2021 ), who analyzed the global genome methylation pattern of canine mammary tumors by immunohistochemistry, described a lower hypermethylation pattern for malignant samples, which is associated with tumor recurrence. In the same way, in mammary tissues as well as in plasma, Lee et al (2019 ) observed a low methylation level in LINE-1, a retrotransposon, in benign and tumor samples when compared with healthy samples.…”
Section: Dna Methylationmentioning
confidence: 99%
“…In the conditions of multiple tumours of the mammary gland, average and overall sizes of malignant tumours are related to non-relapse life (Pecile et al, 2021). The level of methylation of DNA chains (evaluated by 5-methylcytosine) in mammary tumours correlates with size and prognosis for patients (Biondi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%